Living-Wage-Gap and Equalisation analysis (vis-à-vis the U.S.) for selected economies of Asia and Oceania – for all employed in the manufacturing sector– in PPP for private consumption terms 1996-2017 - Jus Semper, La Alianza Global; de Salarios Dignos, Observatorio Internacional (Revista Internacional de Salarios Dignos, 2020)
In 2017 Japan has reversed the downward trend in living-wage equalisation (Eq-Idx) that began in 2013, increasing its Eq-Idx by three points, to a 69 index. This is the result of the combination of the drop of the US hourly rate, an increase of Japan’s hourly rate in local currency (1,9%), a currency devaluation (-2,9%) and the customary drop of PPP cost of living (-3,6%), despite the 1,1% decrease of its hourly rate in US dollars. South Korea sustained the growing trend of its Eq-Idx that resumed in 2014 after a brief downturn in 2013 and is now at 71, three points below its highest index in 2012. This is the result of the combination of the drop of the US equivalent rate, an increase of the local currency rate (1,4%), a currency revaluation of 2,7% that produced a 4% increase of its hourly rate in US dollars despite a 2,8% increase of its PPP cost of living. South Korea has also been able to remain ahead of Japan’s Eq-Idx for the second year. In contrast with Japan and South Korea, Australia continued to decrease its Eq-Idx that began in 2014, with 4,4% drop of its hourly wage rate in local currency, a 3,1% revaluation of its currency and a consequential 1,9% increase in PPP cost of living produced a two-point loss in its Eq-Idx. By the same token, a strong drop of Singapore’s hourly wage rate in local currency (-4,4%) and a 1,5% increase of its PPP cost of living, produced a 1 point loss in its Eq-Idx position.